Determination of hydroxy metabolites of polychlorinated biphenyls in plasma and tissue by gas chromatography/mass spectrometry - Hong, Jee Eun; Pyo, Heesoo; Park, Song-Ja; Lee, Won (ELSEVIER SCIENCE BV, 2007)
This study examines a novel sample preparation method for the determination of 11 hydroxy metabolites of polychlorinated biphenyls (PCBs) in plasma and organ tissues, followed by gas chromatography with mass spectrometric detection (GC/MS). The clean-up method was optimized to eliminate the interference matter by using a silica column and 10 mL of n-hexane/dichloromethane (4:6, v/v) as an eluent. Solid-phase and solvent extraction procedures were used for the plasma and tissues samples, respectively. Compared to C-18 and C-8 solid-phase, C-2 showed higher extraction efficiency with n-hexane as the eluent for plasma. The hydroxy-PCB extraction recoveries achieved with this combined extraction and clean-up procedure from plasma ranged from 87 to 117%, while those from tissues ranged from 82 to 111%. The linear detector responses for propyl derivatives of hydroxy-PCBs were obtained with the coefficients of determination varying from 0.992 to 0.998 in the concentration range of 0. 1-20 ng mL(-1). The method detection limits ranged from 0. 1 to 0.5 ng niL(-1) 1mL of plasma and from 0. 1 to 0.5 ng g(-1) in 1g of tissues. This procedure was successfully applied to the study of 3-OH-2,3',4,4',5-PeCB in rat plasma and liver samples after intraperitoneal injection (20 mg/kg) of 2,3',4,4',5-PeCB. (C) 2007 Published by Elsevier B.V.
Keywords: METHYL SULFONE METABOLITES; SOLID-PHASE EXTRACTION; HUMAN-MILK; LIQUID EXTRACTION; MASS-SPECTROMETRY; PCB METABOLITES; DERIVATIZATION; 2,4' ,5-TRICHLOROBIPHENYL; IDENTIFICATION; METHIONINE